Challenges and opportunities in pediatric residency: an analysis of the increasing number of residents in Italy - Antonio Corsello; Silvia Rotulo; Andrea Santangelo; Alfredo Diana; Federico Rossi; Maria Antonietta Catania; Claudia Aracu; Giuseppe Tiralongo; Francesco Pegoraro (BMC, 2024)
Abstract Background Pediatric residency in Italy has undergone significant changes in recent years, with a notable increase in the number of pediatric residents. Exploring the implications of this increase, highlighting disparities in training opportunities, and discussing the broader socio-economic impacts on pediatric healthcare, represent a crucial consideration for the healthcare system in the future. Main Body The Italian National Association of Pediatric Residents ("Osservatorio Nazionale Specializzandi in Pediatria", ONSP) conducted an extensive survey among pediatric residents to assess the current state of pediatric residency. Key findings indicate that 50% of respondents believe the number of residents is excessive for the available training opportunities, leading to concerns about the quality of education and hands-on experience. Despite the increased number of residents, the workload has increased, but up to one-third of residents feel that the autonomy provided by their programs is insufficient. Significant disparities in training quality were found across different regions, with notable shortages in neonatology and pediatric emergency departments. Research opportunities are also limited, with only 17% of residents finding the time allocated to research satisfactory, especially in central and southern Italy. Conclusion The increase in pediatric residents presents both challenges and opportunities. Addressing these challenges through strategic reforms, such as implementing standardized national curricula, investing in training resources and mobility programs, and enhancing research opportunities, is crucial for the future of pediatric residency in Italy. Ensuring high-quality training for all residents is an ethical and practical obligation that will significantly impact pediatric healthcare.